2018
DOI: 10.1021/acs.jpclett.8b02581
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Infrared Absorption Spectroscopy of Bacterial Nitric Oxide Reductase under Electrochemical Control Using a Vibrational Probe of Carbon Monoxide

Abstract: Nitric oxide reductases (NORs) reduce nitric oxide to nitrous oxide in the denitrification pathway of the global nitrogen cycle. NORs contain four iron cofactors and the NO reduction occurs at the heme b/nonheme Fe binuclear active site. The determination of reduction potentials of the iron cofactors will help us elucidate the enzymatic reaction mechanism. However, previous reports on these potentials remain controversial. Herein, we performed electrochemical and surface-enhanced infrared absorption (SEIRA) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…Immediately upon introduction of NO to A (Scheme 1), aband grows at 1757 cm À1 (B). This band shifts to 1728 cm À1 when 15 NO is used (calc.1 725 cm À1 )a nd is consistent with the N-O stretch of {CuNO} 11 .T his value is considerably higher than that observed for the electron-rich Tp R,R' Cu(NO) (1710-1720 cm À1 )b ut is similar to that for the electron-poor Tp CF 3 ,CH 3 Cu(NO) (1753 cm À1 ) [29] and cationic [Tpm tBu,iPr Cu(NO)] + (1742 cm À1 ). [31] Ther elatively high n(N-O) is indicative of the weak d p (Cu)-p*(NO) interaction and suggests that electron distribution in B can be regarded as largely pertaining to formal Cu I and aneutral NOC,similar to the related Tp complexes.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Immediately upon introduction of NO to A (Scheme 1), aband grows at 1757 cm À1 (B). This band shifts to 1728 cm À1 when 15 NO is used (calc.1 725 cm À1 )a nd is consistent with the N-O stretch of {CuNO} 11 .T his value is considerably higher than that observed for the electron-rich Tp R,R' Cu(NO) (1710-1720 cm À1 )b ut is similar to that for the electron-poor Tp CF 3 ,CH 3 Cu(NO) (1753 cm À1 ) [29] and cationic [Tpm tBu,iPr Cu(NO)] + (1742 cm À1 ). [31] Ther elatively high n(N-O) is indicative of the weak d p (Cu)-p*(NO) interaction and suggests that electron distribution in B can be regarded as largely pertaining to formal Cu I and aneutral NOC,similar to the related Tp complexes.…”
Section: Resultssupporting
confidence: 71%
“…One such clue is that the 2 e − ‐reduced state is energetically highly unfavorable. Indeed, many studies find the heme in the bimetallic active site lying more than 200 mV below the standard reduction potential of the electron relay hemes and the non‐heme metals (Fe B or Cu B ) [8–11] . In the case of Cu B , this would entail a transformation from {CuNO} 11 to a radical monoanionic hyponitrite, Cu II ‐N 2 O 2 .− .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the orientation of a nitric oxide reductase on a SAM-coated Au electrode has been determined by SEIRA spectroscopy. 71 By exploiting the high affinity of carbon monoxide to Fe II and following the potential-dependent intensity of the ν(CO) modes, the formal potentials of the binuclear Fe reaction center could be determined. Aside from probing orientations, SEIRA spectros- copy has been applied to monitor formation of a hybrid complex of PSI and a H 2 ase utilized toward photochemical H 2 generation.…”
Section: Accounts Of Chemical Researchmentioning
confidence: 99%
“…In some of the occupied orientations, which varied depending on the charge of the electrode coating, no direct electronic contact with the electrode was possible and the use of redox mediators was required. Moreover, the orientation of a nitric oxide reductase on a SAM-coated Au electrode has been determined by SEIRA spectroscopy . By exploiting the high affinity of carbon monoxide to Fe II and following the potential-dependent intensity of the ν­(CO) modes, the formal potentials of the binuclear Fe reaction center could be determined.…”
Section: Surface-enhanced Vibrational Spectroscopymentioning
confidence: 99%
“…110 It should be noted that two independent electrochemical studies on PaNOR and MhNOR homologues determined different values for the formal midpoint potentials of the metal centers. Kato, Yagi, and co-workers 111 used spectroelectrochemistry (specifically, surface-enhanced infrared spectroscopy) to determine reduction potentials of −0.11 and −0.44 V vs the normal hydrogen electrode (NHE) for Fe B and heme b 3 , respectively. The latter value was found to occur near the onset of electrocatalytic NO reduction, which suggested that NO reduction is initiated at heme b 3 , thus prompting the authors to favor the trans mechanism.…”
Section: Introductionmentioning
confidence: 99%